PHARMACEUTICAL & ANALYTICAL STUDY OF SAMAGUNA BALIJARITA RASA SINDURA - Sorab Gaind,; Pradeep Agnihotri, (International Journal of Ayurveda and Pharma Research, 2020)
Rasasindura is a one of Kuppipakva Rasayana a unique method of preparation and is one such imperative Kupipakwa Rasayana, referred to be Elixir of life. It is formulated by two fundamental substances of Rasashastra i.e., Shudha Parada and Shudha Gandhaka. It is said to be prepared by same process but with different proportion of Gandhaka, and accordingly various forms of Rasasindura are named as Ardhaguna, Samaguna, Dviguna, Triguna, Chaturguna, Panchaguna, Shadguna balijarita Rasasindura, where in, the therapeutic merits of Rasasindura and pharmaceutics of Rasasindura changes according to quantum of Gandhaka.Rasasindura is a Sagandha, Sagni and Bahirdhooma Kupipakwa Rasayana. Samaguna balijarita Rasasindur was prepared with equal quantities of Parada and Gandhaka by Kupipaka method in 20 hours and physicochemical analysis was carried out.Ash values in Samagunabalijarita Rasasindur were found to be 0.02%. Free mercury was nil in Samagunabalijarita Rasasindur where as its traces were present in the Kajjali. Free sulfur traces were present in Samagunabalijarita Rasasindur. Total mercury percentage in Samaguna Kajjali was 36.02%. Total mercury percentage in Samagunabalijarita Rasasindoor was 83.15%. Total sulfur percentage in Samagunabalijarita Rasasindoor was 13.06%. By XRD analysis Samagunabalijarita rasasindur was identified as Cinnabar having Hexagonal crystal structure with primitive lattice.